WOMEN, NATION BUILDING AND JONATHAN’S ADMINISTRATION IN NIGERIA, 2010-2015. - Ibekwe , Juliet Chinenye; Christian, Chidiobi Okechukwu (IJRDO - Journal of Social Science and Humanities Research, 2022)
The GoodluckJonathan’s administration, covered the period of 2010-2015. He completed the tenure of the late former president,Umar Musa Yar’Adua in 2011 and was subsequently elected as the substantive President of Nigeria in the same year which ended in 2015. However, Nigerian women never had it so good like they did or enjoyed during his administration. In all honesty, the administration is obviously one, most Nigerian women will never forget in a hurry. The Jonathan’s programme on women empowerment cut across board as it did not exclude any level of the women folk. During his period in office, Goodluck Jonathan appointed an overwhelming number of the Nigerian women into top political, strategic and sensitive positions. As if that was not enough, he provided a level playing ground and avenues for as many eligible women as possible to fulfill their dreams and contributing their quota to national development. This singular gestures saw many women being elected as Councilors and members of House of Assemblies at both state and national levels. It is on this note that this paper, therefore examine the contributions of these Jonathan’s women (as they are fondly called) in the various capacities in which they functioned as well as their brief profiles. It also highlights some challenges that confronted them while in office. Equally, the paper looked at related concepts of “gender”, “sex” and “Feminism” as they have to do with women or the topic under discourse. It equally made a long list of women that served under Jonathan’s administration of which five of them were randomly selected and discussed because want of space and time. It concluded recommending measures that will enhance women participation in political governance and administration of the country. These according to this paper include saying no to corruption, distinguishing themselves while in office by performing beyond expectation, taking every opportunity to compete with the male counterparts and not waiting to be given the opportunity before they can take part in the political process